Wealth, Health, and Health Services in Rural Rajasthan - Banerjee, Abhijit; Deaton, Angus; Duflo, Esther (American Economic Review, 2004)
What are the determinants of health and of well-being? Income and wealth are clearly part of the story, but does access to health care have a large independent effect, as the advocates of more investment in health care, such as the World Health Organization’s Commission on Macroeconomics and Health (Commission on Macroeconomics and Health, 2001), have argued? This paper reports on a recent survey in a poor rural area of the state of Rajasthan in India intended to shed some light on this issue, where there was an attempt to use a set of interlocking surveys to collect data on health and economic status, as well as the public and private provision of health care.